ANALISIS EKONOMI DAN KELEMBAGAAN HUTAN RAKYAT SISTEM AGROFORESTRI KOMBINASI JENIS POHON SERBAGUNA DAN KAKAO : Suatu studi kasus di propinsi Sulawesi Tenggara - R Marsuki Iswandi; Affendi Anwar; B D Nasendi; Hermanto Siregar (Jurnal Penelitian Hasil Hutan, 1996)
The agroforestry system  is often  undertaken by famers  in Indonesia specifically for  the development  of multi  purpose  tree species in dry land.   Farmers use the agroforeftry  system  because of ils efficient usage of land and labor and to minimize the risk of crop failure.The agroforestry system  in Southeast  Sulawesi  consists  of planting  cocoa  among multi purpose  tree species  (MPTS), like fruit  trees   (such as langsat or durian) and coconut  trees. The average income earned by  farmers  who apply the combination of langsat, coconut and cocoa was Rp  2.378.825,-/ha/year.  The average income earned by farmers  who apply the combination of  durian, coconut  and  cocoa  was  Rp 2.378.827,-/ha/year.  Financially,  the agroforestry  system  with MPTS  in  Southeast  Sulawesi  is  worth undertaking  because  it  is profitable.From the farmers  point  of view,  the marketing of langsat, durian,  coconut and cocoa is not competitive,  since  farmers  are on the weak side in the price information process.   The results of the analysis of price transmision elasticity,  the index of market integration in the short-run and  in  the  long-run,  show  that  the  market  for  the  above  mentioned   commodities  is  not integrated.   The reason for  this is because of  the inefficiency and deficiency in the availability of market information.The institutional system in the marketing process of the commodities offered by the farmersis  relatively  informal.     In  the  marketing  process   of  langsat,  durian  and  coconut,   the relationship between farmers  and traders can be described as clientelism (patron-client).    On the other hand,  in the marketing of cocoa,  the  farmers  have a fixed  relationship with their market  institutions  like papalele,   whereby  the farmers   receive  working capital from   local traders to harvest and to produce and sale the cocoa to the local market.Key words  :  private  forest,  agroforestry,   MPTS,  income,   marketing,   institution,   Southeast Sulawesi.